THE QUALITY OF WORK LIFE AND SOCIALLY RESPONSIBLE ACTIONS DIRECTED AT EMPLOYEES ON THE EXAMPLE OF A SERVICE COMPANY - Anna Jakubczak; Małgorzata Gotowska (Acta Scientiarum Polonorum. Oeconomia, 2015)
The aim of the study was to describe the implementation of socially responsible business actions addressed to employees in five areas. The two hypothesis has been assumed: 1. The analyzed company acts in social responsibly way towards the employees shaping their quality of work life; 2. Social responsible actions aimed to employees are influencing their quality of life and are important factor of financial success of the company. The original internal data from enterprise and data from other research were analyzed. The main method of research was case study. Data have been obtained through in-depth interviews. Elements of human resource management (HRM) in the enterprise have been characterized. The research found the level of implementation of the concept of corporate social responsibility (CSR) towards internal stakeholders and its importance in shaping the quality of work life.